The 2 min step test: A reliable and valid measure of functional capacity in older adults post coronary revascularisation. (25th November 2022) - Chow, Jaclyn Jie Ling; Fitzgerald, Claire; Rand, Sarah
Abstract: Purpose: Exercise training is the central component in Cardiac Rehabilitation (CR). A baseline assessment of aerobic capacity is paramount for exercise prescription and safety. The Two‐Minute Step Test (2MST) has been used to measure aerobic capacity in healthy older adults. However, the reliability and validity of the 2MST in older adults post‐coronary revascularisation (CRV) is unknown. Methods: A prospective observational study was conducted in a single CR centre. Two 2MSTs and one six‐minute walk test (6MWT) were completed in a single session. The 2MST measurements were recorded by two raters for each individual. The six‐minute walk distance (6MWD) and 2MST steps recorded by both raters were analysed to determine the relationship and agreement between measurements. Results: Thirty one participants with a median (IQR) age of 66 (62, 73) years old were included in the study post CRV. Strong positive correlations were found between steps achieved during the 2MSTs and the 6MWD ( r  = 0.87, 95% CI 0.82–0.91, p  < 0.0001). Excellent inter‐rater reliability was demonstrated between raters during the 2MSTs (ICC = 0.999–1.000, p  = 0.000). Excellent relative test‐retest reliability was demonstrated in both 2MSTs recorded by both raters (ICC = 0.927–0.934, p  = 0.000). However, absolute test‐retest reliability may have been limited by a learning effect between repeated 2MSTs. Conclusions: The results of this study indicate that the 2MST may be used as an alternative to the 6MWT as an outcome measure for aerobic capacity in older adults post‐CRV. However, a practice trial is recommended at baseline to account for a learning effect.